Assessment of storage stability of essential oil enriched flavoured milk - Samaddar, Manalee; Ram, Chand; Sen, Munmun (Indian Journal of Dairy Science, 2015)
Health conscious consumers are more concerned about adverse effect of synthetic preservatives in food. So as an alternative, natural preservatives like plant essential oil components having antimicrobial activity against pathogenic and spoilage microorganism can be used in food products. No study exists on flavoured milk enriched with plant derived essential oil component. So in the present study, essential oil enriched flavoured milk (eugenol and trans-cinnamaldehyde enriched) were assessed for stability during refrigerated storage. Level of essential oil components were standardized for preparation of flavoured milk. Storage studies revealed that enriched flavoured milk having increased antioxidant activity of the product which ultimately enhances the shelf life of the product. Thus, the essential oil enriched flavoured milk is proved as a value added product with enhanced food safety and health attributes as well as it would protect the health of consumers vis-Ã -vis health of the nation.